IBN KHALDUN'S EDUCATIONAL THOUGHTS AND THEIR RELEVANCE TO ISLAMIC BASIC EDUCATION - Ikhsan, Moh. Hayatul (Jurnal Asy-Syukriyyah, 2024)
This research focuses on Ibn Khaldun's thoughts about education and its relevance to the basic education system. In the development of education in Indonesia, secular thinking dominates, which results in the breakdown of the unity of personality. Ibnu Khaldun, apart from being a scientist and historian, was also a phenomenal figure in Islamic education. This research describes the concept of education according to Ibn Khaldun, including educational objectives, students, educators, learning methods, curriculum, and educational environment. The research method used is literature study with reference to Ibn Khaldun's phenomenal work, namely the book "Al-Muqaddimah," as well as other books that examine his thoughts. The main conclusion from this research is that there is relevance between Ibn Khaldun's concept of education and the national education system, especially basic education, so that this idea can be a reference for the development of basic education in Indonesia.